Assessing the Risk of Private Sector Debt Overhang in the Baltic Countries - Herzberg, Valerie (IMF Working Papers; Working Paper ;, 2010)
Between 2000 and 2007 nonfinancial private sector credit expanded rapidly in the Baltic countries, resulting in a non-negligible build-up of debt. Could this legacy debt hold back the economic recovery of the region? This paper analyzes the setting in each of the three countries and, with the help of an experimental Debt Overhang Index (DOI), draws tentative conclusions for domestic demand.